Contribution of microbial activity and vegetation cover to the spatial distribution of soil respiration in mountains - Sushko, Sofia; Ovsepyan, Lilit; Gavrichkova, Olga; Yevdokimov, Ilya; Komarova, Alexandra; Zhuravleva, Anna; Blagodatsky, Sergey; Kadulin, Maxim; Ivashchenko, Kristina (Frontiers in Microbiology, 2023)
The patterns of change in bioclimatic conditions determine the vegetation cover and soil properties along the altitudinal gradient. Together, these factors control the spatial variability of soil respiration (RS) in mountainous areas. The underlying mechanisms, which are poorly understood, shape the resulting surface CO2 flux in these ecosystems. We aimed to investigate the spatial variability of RS and its drivers on the northeastern slope of the Northwest Caucasus Mountains, Russia (1260–2480 m a.s.l.), in mixed, fir, and deciduous forests, as well as subalpine and alpine meadows. RS was measured simultaneously in each ecosystem at 12 randomly distributed points using the closed static chamber technique. After the measurements, topsoil samples (0–10 cm) were collected under each chamber (n = 60). Several soil physicochemical, microbial, and vegetation indices were assessed as potential drivers of RS. We tested two hypotheses: (i) the spatial variability of RS is higher in forests than in grasslands; and (ii) the spatial variability of RS in forests is mainly due to soil microbial activity, whereas in grasslands, it is mainly due to vegetation characteristics. Unexpectedly, RS variability was lower in forests than in grasslands, ranging from 1.3–6.5 versus 3.4–12.7 µmol CO2 m-1 s-1, respectively. Spatial variability of RS in forests was related to microbial functioning through chitinase activity (50% explained variance), whereas in grasslands it was related to vegetation structure, namely graminoid abundance (27% explained variance). Apparently, the chitinase dependence of RS variability in forests may be related to soil N limitation. This was confirmed by low N content and high C:N ratio compared to grassland soils. The greater sensitivity of grassland RS to vegetation structure may be related to the essential root C allocation for some grasses. Thus, the first hypothesis concerning the higher spatial variability of RS in forests than in grasslands was not confirmed, whereas the second hypothesis concerning the crucial role of soil microorganisms in forests and vegetation in grasslands as drivers of RS spatial variability was confirmed.